2017
DOI: 10.3390/ijms18092016
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Inflammatory Response in the Tumor Microenvironment

Abstract: Cell death is the last fate of the life cycle of cells. Different pathways involved in cell death are known to date, and are mostly represented by apoptosis, necrosis, and autophagy. Autophagy is one of the most preserved cell death pathways, characterized by the elimination of large parts of cytoplasmic components after being consumed by a double-membraned vesicle called an autophagosome. The formed autophagosome then fuses with a lysosome containing degrading enzymes and leads to the digestion of the autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 95 publications
1
41
0
1
Order By: Relevance
“…This correlation between IL-6-mediated carcinogenesis and autophagy may represent an interesting and promising approach to treat iCCA with an inflammatory component. Additionally, there are a large number of studies that relate different pro-inflammatory pathways with ER stress and autophagy [79,81,82].…”
Section: Cholangiocarcinoma Genetic and Epigenetic Alterations And Aumentioning
confidence: 99%
“…This correlation between IL-6-mediated carcinogenesis and autophagy may represent an interesting and promising approach to treat iCCA with an inflammatory component. Additionally, there are a large number of studies that relate different pro-inflammatory pathways with ER stress and autophagy [79,81,82].…”
Section: Cholangiocarcinoma Genetic and Epigenetic Alterations And Aumentioning
confidence: 99%
“…However, MALAT1 effect on the interaction between stromal and cancer cells have been rarely studied. Autophagy is a biological process involved with interaction between different types of cells through production of in ammatory mediators [6,20], which can regulate complex multicellular interactions within TME. Several studies have reported that MALAT1 could promote autophagy in various cancers, including retinoblastoma [13], lung cancer [25], and pancreatic cancer [11].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is an important biological process that appears to be a double-edged sword with respect to cytokine signalling and modulating tumour progression in certain instances [5]. Activated autophagy could protect cells from in ammatory damage by inhibiting autophagy and aggravating in ammatory responses in many tissues [5,6]. It is widely accepted that autophagy defects contribute to in ammation and autophagy inhibition under the condition of chronic in ammation devoted to oncogenesis [7,8].…”
mentioning
confidence: 99%
“…Tumour progression in the TME is greatly associated with the onset of inflammation (Coussens et al, 2002). Chronic inflammation favourably promotes tumorigenesis and enhances the ability of cancer cells to metastasize (Ngabire & Kim, 2017 et al, 2008).…”
Section: The Role Of Autophagy In the Tumour Microenvironment (Tme)mentioning
confidence: 99%
“…Inflammatory cytokines such as IL-6, IL-10 and TGF-β are released by TAMs and contributes to the development of cancer by limiting apoptosis in the TME. Cytokines therefore play a major role in the development of chronic inflammation to generate a pro-tumour response(Ngabire & Kim, 2017). Chronic inflammation is generally also associated with an increase in oxidative stress which activates NF-kB to stimulate the onset of autophagy to allow cancer cell growth(Joven et al, 2014).…”
mentioning
confidence: 99%